CAG Expansion in Androgen Receptor Gene of Infertile Men in Erbil Governorate - Salih, Dashne Abdulla; Karim, Karim Jalal (Kurdistan Journal of Applied Research, 2023)
Spermatogenesis and male phenotypic development during puberty are mainly done by androgen and their function is regulated by the androgen receptor (AR) gene. This gene has a polymorphism site in Exon1 which encode androgen receptor and have various length of CAG trinucleotide repeat which causes the production of polyglutamine chain in different length of the N-terminal domain of AR protein which reduces producing sperm by disrupting spermatogenesis. The aim is to determine the relation of infertility in male with the increased frequency of CAG repeats in the AR gene, and the correlation between CAG repetition and hormonal changes. The case-control research was carried out in the Immunogene center and IVF center in the maternity teaching hospital Erbil-Kurdistan region-Iraq. The convenience sample included 50 men, 30 infertile and 20 fertile over one year starting from March 2021 to March 2022. Men with infertility had CAG repeats in their AR gene, ranging from (17-26) repeats, with a mean (21.3 ±0.16). In infertile men, CAG expansion was longer than the fertile men. The motility and normal morphology of sperm in infertile men have negative relation while sperm count and concentration have a positive relation with CAG expansion. The relation of hormones (Testosterone, LH, and FSH) with CAG repetition was statistically not significant. In conclusion, CAG expansion was longer in infertile (case) men compared with fertile (control) men. Polyglutamine effect on increasing sperm abnormal morphology and immotility which is the reason for infertility but statistically not significant and it will not affect hormonal assay in infertile men.